Legal Protection In Fulfilling The Rights And Obligations Of Workers Certain Time Work Agreement - Putri, Shyva Syawa Permata; Tien F, Mas Anienda (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This paper aims to know and analyze workers' rights and the implementation of legal protection in accordance with the Manpower Law. Empirical juridical type data and research using qualitative analysis methods, namely research obtained data through interviews, literature studies, legal journals, and legislation. In PKWT Hotel Sofia Juanda, there are several articles that have not been clearly regulated related to rights and obligations that are incomplete and many are not in accordance with the elaboration of the Manpower Law so that the fulfillment of their rights needs to be included in several new articles. The implementation of legal protection for PKWT workers does not always run well and experiences a number of obstacles caused by lack of awareness and understanding regarding the rights and obligations of each party. In addition, it is caused by limited information. Therefore, efforts to implement the legal protection of PKWT workers at the Sofia Juanda Hotel Surabaya can be carried out through 2 (two) efforts, namely preventive and repressive.